Prawo a wartości w teorii prawa Józefa Nowackiego - Tkacz, Sławomir (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The contents of the paper present the basic assumptions of Józef Nowacki’s theory of law. The author was a proponent of Hans Kelsen’s theory. The characteristic of Józef Nowacki’s views was the conviction that the foundations of the study of the aw should be their „purity”. It is understood by him as freedom from any ideological assumption. This approach is consistently presented in his works dealing with issues of a specific nature. In the course of deliberations, the problem of the concept of law was discussed, as understood by Józef Nowacki. His works on the issues of the rule of law were also analyzed. Moreover, they presented his critical attention devoted to the jurisdiction of the Polish Constitutional Court. The conclusions highlight the validity of the author’s view that the consideration of the law should be free of any ideological assumptions